Asthma and allergies correlate with mental health problems in preschool children. (22nd December 2020) - Edvinsson Sollander, Sofia; Fabian, Helena; Sarkadi, Anna; Salari, Raziye; Fält, Elisabet; Dahlberg, Anton; Feldman, Inna; Durbeej, Natalie
Abstract: Aim: To explore the relations between asthma, allergies and mental health problems in preschool children, aged 3‐5 years. Methods: In this cross‐sectional Swedish study, we used data on 4649 children in Uppsala municipality whose parents and preschool teachers had responded to questions measuring asthma and allergies, and the Strengths and Difficulties Questionnaire (SDQ) for assessment of mental health problems. Logistic regression models were used to explore the relations between asthma and allergies and mental health problems. Results: Children with asthma (8.5%) had elevated odds of having emotional symptoms as rated by parents (OR: 1.34; 1.02‐1.76) and teachers (OR: 1.44; 1.09‐1.91). According to parents' ratings, these children also had elevated odds of showing mental health problems in general according to the SDQ total score (OR: 1.42; 1.05‐1.94). Children with food allergies or intolerance (4.4%) only had elevated odds of having emotional symptoms (OR: 1.64; 1.16‐2.33), as reported by parents. These results remained significant after adjustment for parental background factors. Conclusion: Preschool children with asthma and food allergies or intolerance are at risk of having concurrent mental health problems. Mental health problems should be assessed in children with these disorders. Adequate support and/or referral to specialised services should be offered when needed.